2016
DOI: 10.18632/oncotarget.9329
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between the HIF-1 and Toll-like receptor/nuclear factor-κB pathways in the oral squamous cell carcinoma microenvironment

Abstract: Hypoxia is a prominent feature of the microenvironment of solid tumors and may contribute to tumor progression through the oxygen-sensitive transcriptional regulator hypoxia-inducible factor-1 (HIF-1). Chronic inflammation is another typical feature. Inflammatory mediators, including Toll-like receptors (TLRs) and nuclear factor-κB (NF-κB), play an important role in cancer development. Recent studies have revealed extensive cross-talk between hypoxia and inflammation signaling, though the mechanisms remain unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 39 publications
3
43
0
Order By: Relevance
“…38 Tumor hypoxia has been widely recognized as a major factor for chemoresistance. 11,39 So far, many attempts have been made to enhance the efficacy of Pt by using adjuvants, drug combinations, and nanomedicine systems. For instance, survivin inhibitor YM155 and 3′,4′,5′,5,7-pentamethoxyflavone were shown to have the ability to sensitize cancer cells to CDDP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Tumor hypoxia has been widely recognized as a major factor for chemoresistance. 11,39 So far, many attempts have been made to enhance the efficacy of Pt by using adjuvants, drug combinations, and nanomedicine systems. For instance, survivin inhibitor YM155 and 3′,4′,5′,5,7-pentamethoxyflavone were shown to have the ability to sensitize cancer cells to CDDP.…”
Section: Discussionmentioning
confidence: 99%
“…10 In accordance with previous reports, our group has also demonstrated that tumor hypoxia promotes OSCC resistance to the treatment of CDDP, with hypoxia inducible factor-1α (HIF-1α) acting as a key mediator. 11,12 Tumor microenvironment is a double-edged sword, because facts have proved that these special endogenous properties inside the tumor can be applied to trigger the release of cancer therapeutics. 13 Vascular abnormalities and tumor metabolic activity seek increased glycolysis.…”
Section: Introductionmentioning
confidence: 99%
“…TLR-9/MyD88 signaling pathway plays an important role in hypoxia and inflammatory responses, the expression of HIF-1α and VEGF (14), differentiation and activation of immune cells (15), and release of inflammatory factors such as IL-6 and TNF-α (16). In addition, TLR-9/MyD88 signaling pathway can mediate the transcription of NF-κB, whereas upstream promoter region of NF-κB contains HIF-1α binding site, which can affect the transcription and expression of HIF-1α, so NF-κB can participate in HIF-1α-regulated tumor cell proliferation and apoptosis and other biological activities (8,17).…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1alpha regulates CAIX under hypoxic conditions (12). TLR activation stimulates the expression of HIF-1alpha through NF-jB -signaling in oral cancer, (13) while studies in breast and brain cancers indicated upregulation of TLR9 expression in hypoxia via HIF-1alpha (14), suggesting cross talk between TLR and HIF-1alpha signaling, i.e. innate immunity response and hypoxia.…”
mentioning
confidence: 99%